Towards a telecentre ecosystem for value creation - Md Dahalin, Zulkhairi; Ibrahim, Huda; Yusop, Nor Iadah (2013)
This paper proposes a telecentre ecosystem that can transform the current state of ICT adoption in rural areas into a situation where the community can reap the benefit of access to ICT. Although many initiatives have been implemented to bring access of ICT and the Internet to the rural communities, there appears to be a lack of value added benefit that the community can gain from the adoption of ICT. This paper therefore aims to present a telecentre ecosystem that can transform rural areas into a community that is capable of adding value as a result of ICT. Based on a case study of a telecentre involving respondents from twelve neighboring villages in the northern region of Malaysia, information needs of the local community were identified and prioritized. A telecentre ecosystem was proposed to match the information priority that can optimize the roles of the various stakeholders within the ecosystem.